Dietary diversity and diet quality with gestational weight gain and adverse birth outcomes, results from a prospective pregnancy cohort study in urban Tanzania. Issue 2 (14th December 2021) - Yang, Jiaxi; Wang, Molin; Tobias, Deirdre K.; Rich‐Edwards, Janet W.; Darling, Anne‐Marie; Abioye, Ajibola I.; Noor, Ramadhani A.; Madzorera, Isabel; Fawzi, Wafaie W.
Abstract: Healthy maternal diets during pregnancy are an important protective factor for pregnancy‐related outcomes, including gestational weight gain (GWG) and birth outcomes. We prospectively examined the associations of maternal dietary diversity and diet quality, using Minimum Dietary Diversity for Women (MDD‐W) and Prime Diet Quality Score (PDQS), with GWG and birth outcomes among women enrolled in a trial in Tanzania ( n = 1190). MDD‐W and PDQS were derived from a baseline food frequency questionnaire. Women were monthly followed until delivery, during which weight was measured. GWG was classified based on the 2009 Institute of Medicine guidelines. Adverse birth outcomes were classified as low birth weight (LBW), small for gestational age, large for gestational age, and preterm birth. 46.2% participants had MDD‐W ≥ 5. Mean score of PDQS was 23.3. Maternal intakes of nuts, poultry, and eggs were low, whereas intakes of sugar‐sweetened beverages and refined grains were high. MDD‐W was not associated with GWG or birth outcomes. For PDQS, compared to the lowest tertile, women in the highest tertile had lower risk of inappropriate GWG (risk ratio [RR] = 0.93, 95% confidence interval [CI]: 0.87–1.00). Women in the middle tertile group of PDQS (RR = 0.72, 95% CI: 0.51–1.00) had lower risk of preterm birth. After excluding women with prior complications, higher PDQS was associated with lower risk of LBW (middle tertile: RR = 0.55, 95% CI: 0.31–0.99, highest tertile: RR = 0.52, 95% CI: 0.29–0.94; continuous per SD: RR = 0.77, 95% CI: 0.60–0.99). Our findings support continuing efforts to improve maternal diet quality for optimal GWG and infant outcomes among Tanzanian women. Key messages: Maternal diets are a key modifiable determinant of gestational weight gain (GWG) and birth outcomes. We observed suboptimal intakes of healthy proteins and fats and high intakes of refined grains and sugar‐containing foods among well‐nourished pregnant women in urban Tanzania. This study found that higher‐quality maternal diets were associated with lower risks of inappropriate GWG, low birth weight, and preterm birth. This study supports the importance of high maternal diet quality and continuing efforts to promote well‐balanced maternal diets with avoiding both under‐ and over‐nutrition for optimal pregnancy outcomes among Tanzanian populations.